Efektivitas Penggunaan Channel Youtube dalam Meningkatkan Penguasaan Vocabulary Siswa di Madrasah Tsanawiyah Miftahul Huda - Andri Maulana (Neolectura, 2023)
This study aims to examine the improvement on the vocabulary comprehension of English as foreign language students at MTS Miftahul Huda using Youtube. The study also tries to investigate the students’ perceptions towards the integration of YouTube video on improving students’ vocabulary master. There approximately hundreds of intermediate-level students aged between 12-14 years old participated in the study. Students were divided into two groups: an experimental group that watch YouTube videos during the reading assessment, learning process and a control group that was not exposed to the videos. In addition to questionnaires, pre and post-tests were utilized to collect information. The results of the analysis indicate that the group that viewed YouTube clips fared better on the posttest than the control group that did not view YouTube clips. The result showed that youtube video is able to support the improvement of the students’ vocabulary mastery. According to the results of the research, the participants had favorable opinions toward the integration of YouTube into their respective classes. Additionally, the data revealed a discernible rise in the level of vocabulary achievement attained by the children. In this section, the ramifications of the findings are examined with regard to the process of learning and teaching foreign languages.